2007
DOI: 10.1016/j.surfcoat.2006.08.113
|View full text |Cite
|
Sign up to set email alerts
|

Plasma assisted techniques for deposition of superhard nanocomposite coatings

Abstract: Various techniques based on plasma application have been successfully used for deposition of superhard nanocomposite coatings. These techniques possess many varying parameters, which in turn influence the properties of a growing coating. Therefore it is important to reveal common regularities, if any, between the process parameters and properties of the coatings. The paper addresses this issue based on the results acquired by the application of plasma assisted CVD and PVD methods. Here it is shown how differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…Recent reviews on various deposition technologies can be found in refs. [59,60]. Compared with PECVD, PVD has many advantages such as the low deposition temperature, which allows the processing of low temperature substrate materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews on various deposition technologies can be found in refs. [59,60]. Compared with PECVD, PVD has many advantages such as the low deposition temperature, which allows the processing of low temperature substrate materials.…”
Section: Introductionmentioning
confidence: 99%
“…A more effective alternative method to manufacture heat-generating clothing is to use plasma-assisted metal coating (PAC) (Schneider et al , 2000; Shea, 2005; Martinu et al , 2010; Lilioara et al , 2019). Through this technology, the metal can be directly and equally plated on the cloth surface, the minimum thickness can be controlled in nano-scale, and the treated cloth can maintain its softness without damaging the original physical properties such as tensile strength and texture (Levchuk, 2007; Wang et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the sputtered particles are mainly composed of neutrals and so it is difficult to optimize the particle trajectories for better surface properties. Ionized physical vapor deposition (IPVD) has attracted more interest recently since it may produce better adhesion between the film and substrate in addition to providing better flexible process control [1][2][3][4][5][6][7]. It is also possible to treat irregularly-shaped components due to the high plasma density.…”
Section: Introductionmentioning
confidence: 99%